Objective and Subjective Factors in The Implementation of The Concept of National Ascent - Ilhom Kholmirzaevich Mavlonov (Research Parks Publishers, 2021)
We can see the objective and subjective factors in the implementation of the concept of national growth mainly in the initiatives, in the new, ambitious reforms under the leadership of our President for the sake of the people of Uzbekistan. The process of national development in Uzbekistan is a bright example for the basic reforms being carried out in all the fields in our country in the last years during the globalization period, rapid progress and firm struggles and competitions in all the branches. On the basis of the priority tasks set out in the strategy of actions on the development of our country, developing the national ideology has become an actual issue. We are not mistaken to say that the strategy of actions is our national strategy. Young people have always been the backbone of the nation. If we pay attention to the early period of the last century of the history of our country, then the hearts and minds of the youth were full of the desire for enlightenment. The youth of our country put forward progressive ideas, published newspapers and magazines, opened schools, staged theatrical performances, and established charitable societies